The effect of probiotics, prebiotics and synbiotics on gut microbial community profile in overweight and obese Latin American and Caribbean populations: a systematic review of human trials - Manahil M. Bineid; Litai Liu; Eduard F. Ventura; Sakshi Bansal; Katherine Curi-Quinto; Juana del Valle-Mendoza; Gemma E. Walton; Karani Santhanakrishnan Vimaleswaran (Gut Microbiome)
Oral supplementation with probiotics, prebiotics, and synbiotics is a novel potential complementary therapy for addressing overweight and obesity through gut microbiota modulation. This systematic review provides a comprehensive summary of the existing evidence to guide future research. Literature searches were conducted in four databases to identify human trials published until May 2024 that examined the impact of probiotic, prebiotic, or synbiotic interventions on faecal microbiota composition changes in overweight and obese participants from Latin American and Caribbean populations (LACPs). Of the 13,090 identified records, five randomised controlled trials (RCTs) from Brazil, Mexico, and Chile met the inclusion criteria for this review. The included RCTs evaluated different forms of therapies over short-term interventions (6 or 8 weeks), with sample sizes ranging from 21 to 39 participants across the studies. Variations in the reported outcomes were observed due to differences in supplement formulation, dosage, population characteristics, and methodological heterogeneity. The findings indicate that the available data are inadequate to establish definitive conclusions regarding the impact of biotic treatments on gut microbiota profiles in LACP. Further research with larger sample sizes and precise microbiota analysis is required to elucidate the implications of dietary interventions on gut microbiota in obesity and related disorders.